2022
DOI: 10.3390/en15031124
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of the Aerodynamic Influence of Ground and Wheel States on the Notchback DrivAer

Abstract: This paper conducts an analysis of the aerodynamic influence of different ground and wheel states on the Notchback DrivAer by numerical simulation. The effects of the moving ground and rotating wheels are investigated individually and comprehensively. Experimental data are also included for validation. Through this study, a unique and important low-drag state is observed, in which the vehicle wake near the center region becomes more symmetrical, the pressure on the upper middle base is recovered and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…22, the separation bubbles around the front wheel are larger than those around the rear wheel in both the original and optimized configurations. This implies that the pressure recovery in the front wheel is slower, resulting in higher aerodynamic drag compared to the rear wheel [5,28]. In comparison, the optimized wheel exhibits suppressed flow separation and reduced separation bubble size based on the differences in the iso-surface of zero total pressure coefficient.…”
Section: Aerodynamic Characteristics Of Ahmed Body With Wheelmentioning
confidence: 99%
See 1 more Smart Citation
“…22, the separation bubbles around the front wheel are larger than those around the rear wheel in both the original and optimized configurations. This implies that the pressure recovery in the front wheel is slower, resulting in higher aerodynamic drag compared to the rear wheel [5,28]. In comparison, the optimized wheel exhibits suppressed flow separation and reduced separation bubble size based on the differences in the iso-surface of zero total pressure coefficient.…”
Section: Aerodynamic Characteristics Of Ahmed Body With Wheelmentioning
confidence: 99%
“…Numerous studies have pointed out that wheels have a considerable influence on the aerodynamic properties and can contribute up to 25% of the total drag on modern vehicles. The aerodynamic drag has a direct relationship with the flow field around the car, and the high contribution of wheels to drag is due to the strong interactions between the wheel wake and the vehicle underbody through pressure modifications [5]. Hence, when body shape optimization reaches its limits, wheel aerodynamics becomes a prominent concern in order to reduce fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that proper vehicle design would be necessary to decrease the aerodynamic drag generated at the rear of vehicles [11]. In this sense, the literature identifies works focused on different vehicle devices, such as the state of the wheels [12] or the use of flaps [13]. Since air is a great source of energy in other energy systems such as wind energy, the concern of this research stems from the objective of taking advantage of the great force of the airflow impinging on vehicles, to transform a part of the problem into a competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [24] proposed a wake status they called "wake balance" by comparing the flow field of a square-back model with rotating and stationary wheels. Yu et al [25] investigated the aerodynamic influence of different ground and wheel conditions on the Notchback DrivAer using numerical simulations. Zhou et al [26] experimentally and computationally investigated the aerodynamic characteristics of three tires of the 185/65 R14 type with different patterns under loading by comparing a simplified isolated tread tire with the real complex pattern.…”
Section: Introductionmentioning
confidence: 99%